Thoracic enhanced recovery with ambulation after surgery: a 6-year experience. (23rd March 2018) - Khandhar, Sandeep J; Schatz, Christy L; Collins, Devon T; Graling, Paula R; Rosner, Carolyn M; Mahajan, Amit K; Kiernan, Paul D; Liu, Chang; Fernando, Hiran C
Abstract: OBJECTIVES: Our institution implemented a protocol known as thoracic enhanced recovery with ambulation after surgery (T-ERAS) in thoracic operations. The objective was early ambulation starting in the postoperative ambulatory care unit. METHODS: Video-assisted thoracoscopic surgery lobectomy patients are placed on a chair in the preoperative area and then walked to the operating room. Postoperatively, patients are placed on a chair as soon as possible. Our target ambulation goal was 250 feet within 1 h of extubation. Patients then walk to their hospital room. T-ERAS adoption and outcomes were compared to a pre-T-ERAS period, in addition to the comparing early and late T-ERAS cohorts. RESULTS: Over 6 years, 304 patients on T-ERAS underwent a planned video-assisted thoracoscopic surgery lobectomy. Median age was 67 years (range 41–87 years). The target goal was achieved in 187 of 304 (61.5%) patients and 277 of 304 (91.1%) patients ambulated 250 feet at any time in the postoperative ambulatory care unit. The T-ERAS period had a median length of stay of 1 day vs 2 days in the pre-T-ERAS period ( P < 0.001). There were low rates of pneumonia (2/304, 0.7%), atrial fibrillation (12/304, 4.0%) and no postoperative mortalities for T-ERAS. The target goal was achieved at a greater rate in the late (92/132, 72.0%) versus early (28/75, 37%) T-ERAS cohort. The mean time to ambulation was reduced in the late cohort (46–81 min). CONCLUSIONS: Early postoperative ambulation was feasible and considered key in achieving low morbidity after video-assisted thoracoscopic surgery lobectomy. Adoption of T-ERAS improved over time. Further studies will help define adoptability at other sites and validate impact on improving outcomes.